Biomolecular Chemistry in Liquid Phase Separated Compartments - Nakashima, Karina K.; Vibhute, Mahesh A.; Spruijt, Evan (Frontiers in Molecular Biosciences, 2019)
Biochemical processes inside the cell take place in a complex environment that is highly crowded, heterogeneous, and replete with interfaces. The recently recognized importance of biomolecular condensates in cellular organization has added new elements of complexity to our understanding of chemistry in the cell. Many of these condensates are formed by liquid-liquid phase separation (LLPS) and behave like liquid droplets. Such droplet organelles can be reproduced and studied in vitro by using coacervates and have some remarkable features, including regulated assembly, differential partitioning of macromolecules, permeability to small molecules, and a uniquely crowded environment. Here, we review the main principles of biochemical organization in model membraneless compartments. We focus on some promising in vitro coacervate model systems that aptly mimic part of the compartmentalized cellular environment. We address the physicochemical characteristics of these liquid phase separated compartments, and their impact on biomolecular chemistry and assembly. These model systems enable a systematic investigation of the role of spatiotemporal organization of biomolecules in controlling biochemical processes in the cell, and they provide crucial insights for the development of functional artificial organelles and cells.